2016
DOI: 10.3748/wjg.v22.i41.9229
|View full text |Cite
|
Sign up to set email alerts
|

Collision tumor of hepatocellular carcinoma and neuroendocrine carcinoma involving the liver: Case report and review of the literature

Abstract: Primary hepatic neuroendocrine carcinoma (NEC) with concurrent occurrence of hepatocellular carcinoma (HCC) of the liver is very rare. Only 8 cases have been reported in the literature. Concurrent occurrence of HCC and NEC in the liver is classified as combined type or collision type by histological distributional patterns; only 2 cases have been reported. Herein, we report a case of collision type concurrent occurrence of HCC and NEC, in which primary hepatic NEC was in only a small portion of the nodule, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 9 publications
2
30
0
1
Order By: Relevance
“…We present a case of a liver tumor with features of both classical HCC and NEC. In this case, the patient is young, male, and has a history of hepatitis B, which is consistent with the previous literature [5,6,7], which all featured male patients with underlying liver disease, involving chronic hepatitis or cirrhosis of unknown cause, sometime a fat component [8].…”
Section: Discussionsupporting
confidence: 90%
“…We present a case of a liver tumor with features of both classical HCC and NEC. In this case, the patient is young, male, and has a history of hepatitis B, which is consistent with the previous literature [5,6,7], which all featured male patients with underlying liver disease, involving chronic hepatitis or cirrhosis of unknown cause, sometime a fat component [8].…”
Section: Discussionsupporting
confidence: 90%
“…Although multiple HCC-NEC of the liver has been described in some reports, 6 , 9 , 14 they are solitary lesions and frequently do not metastasize at the time of diagnosis, as seen in our case. Rarely, metastases to lymph nodes and omentum have been described ( Table 2 ).…”
Section: Discussionsupporting
confidence: 52%
“… 7 , 8 , 14 16 , 19 This observation suggested that NEC components strongly affect the aggressive behavior of the tumor and it is proposed that the NEC component may be responsible for the poor prognosis in these patients. 16 , 19 Recently, Choi et al 9 proposed adjuvant chemotherapy to increase life expectancy when the grade of NEC is high. Because the awareness of an NEC component might influence the treatment strategy and eventually the outcome of the patient, 9 , 16 , 19 the possibility of NEC should be considered in HCCs with nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Most hepatic MiNENs contain a component of hepatocellular carcinoma, which may be the dominant component. 5,32,33 Neuroendocrine Neoplasms of the Bile Ducts and Gallbladder…”
Section: Hepatic Neuroendocrine Neoplasmsmentioning
confidence: 99%